Analisis Budaya Organisasional Terhadap Komitmen Kerja Karyawan Dalam Peningkatan Kinerja Organisasional Karyawan - Noor Arifin (Jurnal Ekonomi dan Pendidikan, 2010)
This Study aims to find the influence of organizational culture toward work commitment, organizational culture toward performance, and commitment toward performance employe and customer of BMT in regional Jepara. The main problems is how to influence organizational culture toward performance, and commitment toward work performance. The variable in this research are organizational culture (X1) adopt a model by Robbins (1996). The second Variable in Commitment (Y1) adopt a model by Modway, Porter dan Steers (1998), and variable performance (Y2) adopt a model A.A. Anwar Prabu Mangkunegara (2000). Amount of sample are 90 from employee and customer of BMT in regional Jepara. Analysis was performed using the PLS tool. The result of this research are; there are significant influence of organizational culture toward work commitment this proved research influence of organizational culture toward work commitment toward work performance this proved research by Steers (1998), and commitment toward work performance this proved research by Barret, H, and Balloun, J.L. (2005). But not into organizational culture toward work performance, so that did not proved research by William N. Cooke (2000) in BMT of regional Jepara. Number of R-square commitment variable is explained by construct of organizational culuture are 43% the rest by another factors. And then Number R-square performance variable are explained by construct of organizational culture and work commitment a simultanly are 54,4% the rest by another factor. And the commitment variable to this research a intervening variable on correlation between orgazational culture toward work performance.